“When to Hold and When to Fold”: Simulating Portfolio Returns to Angel Investing in Early Stage Ventures - Bock. Adam J.; Harrison. Richard T.; Gregson. Geoff (Senate Hall, 2022)
We use a large scale simulation to explore returns to angel investing in the context of real-world constraints in the first empirical examination of investment timing, termination and re-investment. Prior studies calculate angel returns as a single portfolio of investments, as if angels make hundreds of investments simultaneously and hold them all until exit or failure. We sample the largest available angel returns data set while varying portfolio size, investing window and portfolio hold time. Our Monte Carlo analysis simulates more than 11 million portfolios with over 240 million hypothetical investments. The results suggest that angel investing presents more variability and lower returns than reported in prior studies. Low returns are also associated with follow-on investment, which suggests that angels may tend to escalate commitment to poorly performing investments. The study highlights the importance of examining angel investing returns in the context of real-world constraints.
Keywords: angel investment|investment returns|escalation of commitment|exits|investment window